2002
DOI: 10.1542/peds.109.6.1068
|View full text |Cite
|
Sign up to set email alerts
|

Second Varicella Infections: Are They More Common Than Previously Thought?

Abstract: Clinical varicella reinfections may occur more commonly than previously thought. Additional studies of the predictive value of a positive varicella history and laboratory studies of reported reinfections are indicated to guide varicella vaccination policy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 22 publications
0
40
1
1
Order By: Relevance
“…VOka establishes latency and can reactivate to cause zoster, and superinfection with wild-type VZV strains has been documented frequently among vaccinated individuals (3, 13-15, 30, 37). In addition, a recent population-based study indicated that second cases of wild-type varicella occur more frequently among naturally infected persons than previously appreciated (19). These findings suggest that recombination between wildtype VZV strains and V-Oka strains is possible in both vaccine recipients and, more rarely, between wild-type viruses in persons dually infected with wild-type strains.…”
Section: Discussionmentioning
confidence: 80%
“…VOka establishes latency and can reactivate to cause zoster, and superinfection with wild-type VZV strains has been documented frequently among vaccinated individuals (3, 13-15, 30, 37). In addition, a recent population-based study indicated that second cases of wild-type varicella occur more frequently among naturally infected persons than previously appreciated (19). These findings suggest that recombination between wildtype VZV strains and V-Oka strains is possible in both vaccine recipients and, more rarely, between wild-type viruses in persons dually infected with wild-type strains.…”
Section: Discussionmentioning
confidence: 80%
“…The viral reactivation of VZV occurs years later, following factors favoring the decrease of the specificanti-cellular immunity anti-VZV. A reactivation as fast in our case is very particular little described in the literature [1,4]. In our patient, the diagnosis of generalized herpes zoster was excluded because there was no history of varicellla before, and because the generalized eruption preceded the zoniform eruption on the Path of the sciatic nerve.…”
Section: Discussionmentioning
confidence: 59%
“…In our patient, the diagnosis of generalized herpes zoster was excluded because there was no history of varicellla before, and because the generalized eruption preceded the zoniform eruption on the Path of the sciatic nerve. The rapid reactivation concomitant with primofection with VZV could be explained by the state of HIV immunodeficiency [4,5]. Indeed, the occurrence of VZV infection in an HIV-positive subject would be statistically associated with a risk of progression of the disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…67 Although national surveillance for varicella cases remains incomplete, active surveillance in limited geographic areas and national mortality data revealed marked decreases in varicella incidence, varicella-related hospitalizations, and deaths in all age groups. 64,[68][69][70] Varicella cases decreased 71% to 84% and mortality decreased by 66%. 70 Cases among vaccinated individuals are now increasing, which is believed to be happening because of waning immunity.…”
Section: Epidemiologymentioning
confidence: 99%